Myostatin promotes the epithelial‐to‐mesenchymal transition of the dermomyotome during somitogenesis. Issue 12 (22nd November 2018) - Zhou, Yuchang; Zhang, Yong; Zhu, Dahai
Abstract : Background : Myostatin (MSTN), a member of the transforming growth factor‐β (TGF‐β) superfamily, has been implicated in the negative regulation of skeletal myogenesis. However, the molecular mechanism through which MSTN regulates early embryonic myogenesis is not well understood.Results : We demonstrate that MSTN regulates early embryonic myogenesis by promoting the epithelial‐to‐mesenchymal transition (EMT) of the dermomyotome during somitogenesis in chicks. We show that the MSTN gene is first expressed at the center of the dermomyotome. As somitogenesis progresses, its expression extends dorsally and ventrally along the plane of the dermomyotome. By combining in situ hybridization and immunofluorescence assays, we demonstrate that the expression pattern of MSTN is spatiotemporally well correlated with EMT of the dermomyotome. Our gain‐ and loss‐of‐function experiments further reveal that MSTN can induce EMT of the chick dermomyotome. We also show that MSTN induces EMT of a nonsmall cell lung carcinoma cell line (A549) and Madin‐Darby canine kidney cells in vitro.Conclusions : Our experimental data suggest that MSTN regulates myogenesis by promoting EMT during somitogenesis. These findings provide novel insights into the functions of MSTN during early embryonic myogenesis. Developmental Dynamics 247:1241–1252, 2018. © 2018 Wiley Periodicals, Inc. Key Findings: MSTN; EMT; chick embryo